MALARIA IN PREGNANCY - Ebako Ndip Takem; Umberto D'Alessandro (Mediterranean Journal of Hematology and Infectious Diseases)
Pregnant women have a higher risk of malaria compared to non-pregnant women. This review provides an update on knowledge acquired in the past decade on P. falciparum and P.vivax infections in pregnancy. Maternal risk factors for malaria in pregnancy (MiP) include low maternal age, low gravidity, and low gestational age. The effects of MIP include maternal anaemia, low birth weight (LBW), preterm delivery and increased infant mortality.